Primary Si refinement and eutectic Si modification in Al-20Si via P-Ce addition - Peerawit Chokemorh; Phromphong Pandee; Suwaree Chankitmunkong; Ussadawut Patakham; Chaowalit Limmaneevichitr (My University, 2022)
Abstract Enhancing the mechanical properties of hypereutectic Al-Si alloys by refining the primary and eutectic Si morphology is very challenging. In this study, the refinement mechanism of primary and eutectic Si morphologies via the simultaneous addition of P-Ce into the Al-20Si alloy was studied. Microstructural analysis revealed that the primary and eutectic Si morphologies were significantly refined, which increased the tensile strength. Furthermore, the addition of Ce, up to 0.6 wt%, can result in the formation of Ce-rich intermetallic phases, which may lead to a significantly increased tensile strength while retaining the ductility of the alloy. The ultimate tensile strength of the Al-20Si alloy increased from 96 to 175 MPa, and the elongation increased from 1.0% to 1.7% with the addition of P-Ce. Moreover, the wear resistance of the alloy improved. The added P and Ce did not react with each other to form an intermetallic compound; therefore, this method can simultaneously refine primary and eutectic Si.
Keywords: Elongation; Ductility (Earth science); Aluminum Alloy Microstructure Properties